A precise measurement of the 117mSn half-life. (January 2017) - Domingo, T.; Starosta, K.; Chester, A.; Williams, J.
Abstractre: The 117m Sn isotope was produced via fast, 14.1 MeV neutron activation of natural tin and studied with a background shielded HPGe detector. To enable time-resolved γ -ray spectroscopy to precisely measure the half-life of 117m Sn, a commercial DAQ was replaced with a CAMAC-based analogue DAQ. The deadtime response of the applied DAQ was verified for the measurement. The half-life of 117m Sn was measured to be 13.91±0.03 days and the I(158.6 keV)/I(156.0 keV) γ -ray ratio was measured to be 43.6±1.5. Highlights: Sn-117m was measured via time-resolved gamma-ray spectroscopy. Event losses due to `busy' or pileup were measured for a deadtime correction. The measured half-life of Sn-117m was determined to be 13.91 ± 0.03 days.